Architecture and organic unity - Hyman, John (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2019)
Buildings and monuments are among the most important works of art. But the conception of the arts that emerged in the 18th century, and remained the orthodoxy in philosophy for about two centuries, either excludes architecture from the fine arts or relegates it to the intermediate or decorative arts. This essay addresses this puzzle, assesses the truth in certain formalist doctrines about architecture, and advances the view that works of art are organic unities, i.e. integrated sets of solutions to various problems, some aesthetic and others technical, mathematical, theological, political, etc.